Simulation and analysis of schottky junction perovskite solar cells (SJPSCs). Issue 1 (March 2021) - Sinha, Numeshwar Kumar; Roy, Priyanka; Ghosh, Dhriti Sundar; Khare, Ayush
Abstract: The Schottky junction solar cells are the simplest and single-layer structure of solar cells, offering low-cost and easy fabrication. In this study, we have simulated and analyzed the Schottky junction perovskite solar cells, having the device structure of FTO/MAPbI3 /Au. The simulation has done by Solar Cell Capacitance Simulator (SCAPS-1D). In this simulation, we have studied the effect of an absorber layer thickness, doping density, defect density, and the cell's temperature on the performance of the cells. We have further studied the effect of different back electrodes, like Au, Cu, Ag, Al, and Graphene in the performance of cells. The effect of series and shunt resistance has also been studied at optimized parameters. This simulation suggests that the SJPSCs show the highest optimized power conversion efficiency of greater than 14%, at actual series and shunt resistance of the cell. Simulating this simplest structure will help to further improvement in the performance of SJPSC. However, the use of lead makes the solar cells non-eco-friendly, but the proper encapsulation and disposal management can solve this problem.